Estratégias de marketing al centro médico cemedefa salud del cantón Yaguachi, periodo 2022 - Ordoñez Soria Deyonaira Deyalith (2023)
The objective of this case study is to analyze the marketing strategies of the Medical Health Center CEMEDEFA SALUD, in the period 2022. From objective and subjective perspectives, it is established how its marketing strategies have influenced the decline in visits from users looking for solutions. to their health problems. It begins with the analysis of its promotional methodology, implementation of digital resources and customer service. It should be noted that the focus of this research focuses on the marketing activities carried out by the medical center of the Yaguachi canton in the period 2022. To obtain results, a mixed methodology is applied, since qualitative and quantitative techniques are implemented. , such as: survey and interview. In this context, this project is supported by the descriptive and deductive method, since we seek to obtain a much broader vision of the situation experienced by the medical center. This research project is of profound relevance for many companies that require taking into account marketing strategies or the creation of brand image. The direct beneficiaries are the managers and administrative staff, while the indirect beneficiaries are the patients and the community. In turn, it is defined as a non cross-sectional research, because it does not receive financial aid from any allied institution.